2018
DOI: 10.1186/s40557-018-0212-5
|View full text |Cite
|
Sign up to set email alerts
|

Marginal socio-economic effects of an employer’s efforts to improve the work environment

Abstract: BackgroundWorkplace health promotion (WHP) strongly requires the employer’s efforts to improve the psychosocial, ergonomic, and physical environments of the workplace. There are many studies discussing the socio-economic advantage of WHP intervention programmes and thus the internal and external factors motivating employers to implement and integrate such programmes. However, the socio-economic impacts of the employer’s multifactorial efforts to improve the work environment need to be adequately assessed.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 22 publications
(38 reference statements)
1
7
0
Order By: Relevance
“…Negative spillover is induced when people manage various roles both in work and life with limited resources so that it can lead to stress and strain [ 18 , 21 ]. These findings are consistent with previous cross-sectional study examining the association of the subjective time balance between work and life with well-being in South Korea [ 43 ]. In our study, Negative spillover includes the difficulty to fulfilling domestic obligation due to long work hours or irregular work schedule and the difficulty to concentrate on work due to parenting, caregiving, or domestic matters.…”
Section: Discussionsupporting
confidence: 93%
“…Negative spillover is induced when people manage various roles both in work and life with limited resources so that it can lead to stress and strain [ 18 , 21 ]. These findings are consistent with previous cross-sectional study examining the association of the subjective time balance between work and life with well-being in South Korea [ 43 ]. In our study, Negative spillover includes the difficulty to fulfilling domestic obligation due to long work hours or irregular work schedule and the difficulty to concentrate on work due to parenting, caregiving, or domestic matters.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with our results, Blanco-Hungría A et al, reported a higher prevalence of TMD among separated and divorced individuals followed by married, and least among the single individual [ 50 ]. Contrary to this, Han W et al, reported single females to have more TMD disorders compared to married contemporaries [ 51 ]. Although married individuals could have additional emotional support, prevailing social, economic and professional demands could challenge their threshold, and offset the balance of personal and professional life.…”
Section: Discussionmentioning
confidence: 99%
“…Of these patients, 35 (89.7%) were men and 4 (10.3%) were women. The primary sites of malignant mesothelioma were the pleura, 23 (28.2%); the peritoneum, 11 (28.2%); and the mediastinum, 2 (5.1%), with the data unknown for 3 patients (7.7%) [ 16 ]. However, there was a limit to grasping the overall scale, as the annual number of cases was less than 10.…”
Section: Discussionmentioning
confidence: 99%